THE INFLUENCE OF BOPO, DPK, MUDHARABAH FINANCING ON FINANCIAL PERFORMANCE WITH CAPITAL STRUCTURE AS AN INTERVENING VARIABLE - Azizah, Nora Wafiq; Sulistyo; Irianto, Mochamad Fariz (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2024)
This study examines the effect of BOPO, DPK, and mudharabah financing on the financial performance of Islamic banking institutions by considering capital structure as a mediating factor. These institutions have obtained official registration from the financial service authority. This quantitative research uses the annual financial report for 2015-2020. The sample of this study consists of 5 Islamic commercial banks that are officially registered with the financial services authority. These companies were selected using purposive sampling. This study analyzes data using path analysis. The research evidence shows that BOPO, DPK, capital structure affect financial performance, but mudharabah financing does not affect financial performance. BOPO and mudharabah financing affect capital structure, but DPK does not affect capital structure. Capital structure is less able to mediate the effect of BOPO and mudharabah financing on financial performance, but capital structure is able to mediate the effect of DPK on financial performance.